2021
DOI: 10.1021/acsnano.1c01379
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Parachute-like Nanomotors for Enhanced Skin Penetration and Synergistic Antifungal Therapy

Abstract: Fungal infections in skin are extremely stubborn and seriously threaten human health. In the process of antifungal treatment, it is a huge challenge that the stratum corneum of the skin and fungal biofilms form the drug transport barrier. Herein, a near-infrared (NIR) laser-propelled parachute-like nanomotor loaded with miconazole nitrate (PNM-MN) is fabricated to enhance transdermal drug delivery for synergistic antifungal therapy. Due to asymmetrically spatial distribution, PNM can generate a thermal gradien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 39 publications
3
55
0
1
Order By: Relevance
“…10 In general, successful topical drug preparation should provide effective accumulation in the skin and maintain local therapeutic concentration at the lesion site. 11,12 Moreover, it is important to adjust the release rate of drugs in order to achieve prolonged pharmacological effect. 13 In spite of the fact that topical antimycotics cover a broad range of therapeutic substances, they are generally highly lipophilic and poorly water-soluble; therefore, they are frequently retained inside the lipidic stratum corneum.…”
Section: Introductionmentioning
confidence: 99%
“…10 In general, successful topical drug preparation should provide effective accumulation in the skin and maintain local therapeutic concentration at the lesion site. 11,12 Moreover, it is important to adjust the release rate of drugs in order to achieve prolonged pharmacological effect. 13 In spite of the fact that topical antimycotics cover a broad range of therapeutic substances, they are generally highly lipophilic and poorly water-soluble; therefore, they are frequently retained inside the lipidic stratum corneum.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, near-infrared (NIR) laser–propelled nanomotors has broad application prospects on complex physiological barrier penetration because of the characteristics of fuel-free and stable motion performance ( 15 , 16 ). Ji et al ( 17 ) reported that the penetration efficiency of nanomotors to the stratum corneum of the skin was 2.5 times higher than that of passive diffusion nanoparticles. The remarkable motility characteristic of nanomotors offers great opportunities for the penetration of intestinal mucus barrier.…”
Section: Introductionmentioning
confidence: 99%
“…[ 148 ] Recently, Ji and co‐workers fabricated a NIR‐propelled parachute‐like nanomotor loaded with miconazole nitrate (PNM‐MN) for synergistic treatment of Candida albicans biofilm in vivo ( Figure A). [ 25 ] The NIR propulsion of PNM‐MN is derived from self‐thermophoresis subjected to a temperature gradient, which effectively enhances its penetration into the skin. The combination of pharmacological and photothermal effects resulted in synergistic antifungal therapy in C. albicans infected mice.…”
Section: Advanced Micro/nanorobotic Strategy For Biofilm Removalmentioning
confidence: 99%
“…Reproduced with permission. [ 25 ] Copyright 2021, American Chemical Society. B) Magnetic photodynamic nanoplatforms for the treatment of periodontal disease.…”
Section: Advanced Micro/nanorobotic Strategy For Biofilm Removalmentioning
confidence: 99%
See 1 more Smart Citation